Confidence measurement in the light of signal detection theory - Massoni, Sébastien; Gajdos, Thibault; Vergnaud, Jean-Christophe (Frontiers in Psychology, 2014)
We compare three alternative methods for eliciting retrospective confidence in the context of a simple perceptual task: the Simple Confidence Rating (a direct report on a numerical scale), the Quadratic Scoring Rule (a post-wagering procedure) and the Matching Probability (a generalization of the no-loss gambling method). We systematically compare the results obtained with these three rules to the theoretical confidence levels that can be inferred from performance in the perceptual task using Signal Detection Theory. We find that the Matching Probability provides better results in that respect. We conclude that Matching Probability is particularly well suited for studies of confidence that use Signal Detection Theory as a theoretical framework.